Zipper encodes a putative integral membrane protein required for normal axon patterning during Drosophila neurogenesis. - Zhao, D B (1988)
During the development of the central nervous system, Drosophila embryo axons become organized in a stereo-typed fasciculation pattern. We have found that the zipper (zip) gene, initially identified on the basis of a defective larval cuticle in zip mutant embryos, is possibly involved in the establishment or maintenance of the axon pattern during the late stages of neurogenesis. The zip wild-type gene is expressed in the developing nervous system. It codes for a putative integral membrane protein. Both the molecular features of zipper and its biological effect in the nervous system of mutants suggest that zipper is an essential component for cell surface interactions involved in axon patterning, and that the cuticle phenotype of zip mutants is dependent on the primary defects observed in the nervous system.